2015
DOI: 10.1186/s40880-015-0006-x
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment platelet count improves the prognostic performance of the TNM staging system and aids in planning therapeutic regimens for nasopharyngeal carcinoma: a single-institutional study of 2,626 patients

Abstract: IntroductionThrombocytosis has been identified as an unfavorable prognostic factor in several types of cancer. This study aimed to evaluate the prognostic value of pretreatment platelet count in association with the TNM staging system and therapeutic regimens in patients with nasopharyngeal carcinoma (NPC).MethodsA total of 2,626 patients with NPC were retrospectively analyzed. Platelet count >300 × 109/L was defined as thrombocytosis. Matched-pair analysis was performed between patients receiving chemoradioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 26 publications
1
31
0
1
Order By: Relevance
“…Chen et al [23] reported that pretreatment increased platelet count was an unfavorable prognostic factor for NPC patients. In this study, a relatively high PLR was associated with short survival in NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [23] reported that pretreatment increased platelet count was an unfavorable prognostic factor for NPC patients. In this study, a relatively high PLR was associated with short survival in NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, we explored the prognosis only according to anatomic factors in this study. An increasing number of biological, genetic, and molecular factors, such as plasma/serum Epstein–Barr virus (EBV) DNA [34] and specific microRNAs (miRNAs) [35], as well as the target volume [36, 37] and other non-anatomic factors, have been identified and studied [38]. Such factors may have profound influences on the prognosis for individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…ABC transporters are recognized as chief culprits in the development of MDR. Therapies continue to be developed with the goal of blocking or inactivating ABC transporters to increase the concentration of anticancer drugs within cells [46]. …”
Section: Mechanisms Of Mdrmentioning
confidence: 99%